CATASTROPHE BOND MODELING WITH A NONHOMOGENEOUS POISSON PROCESS AND GENERALIZED PARETO DISTRIBUTION: CASE STUDY OF FLOOD NATURAL DISASTER IN THE PEOPLE'S REPUBLIC OF CHINA - ATHAR ISWANDI, MUHAMMAD
A Catastrophe Bond (CAT Bond) is a type of Insurance Linked Security (ILS) with the payment of the Principal or the Face Value to the investors at the maturity date dependent upon the occurrence or the non-occurrence of the underlying natural disaster during the period of the investment. In the context of a general insurance business, a reinsurance company that covers natural disaster insurance claims uses a CAT Bond to transfer the risk of financial losses due to a natural disaster not only to a larger reinsurance company, but also to a capital market. In this Final Project, a CAT Bond modeling is carried out which is linked to a flood natural disaster in the People's Republic of China (PRC). The data on the flood events and the corresponding financial losses in PRC were taken from the Emergency Events Database (EM-DAT) for the period of January 2012 to December 2021. The data were then cleaned and 86 observations were obtained and analyzed. To model the occurrence of the flood natural disaster, a non-homogeneous Poisson process is used; and to model the corresponding financial losses, the peak-over-threshold (POT) approach is used, hence modeled by a generalized Pareto distribution. The CAT Bond modeling is carried out following a scenario in which the coupon rate is calculated as the sum of the premium and LIBOR; the maturity periods applied are 1, 3, and 5 years; and the trigger used is the indemnity trigger. Several simulations were carried out to observe: the profit received by the Issuer; the expenses by the Sponsors; and the returns received by the Investors. The issued CAT Bond succeeded in: reducing the risk of financial losses which could be suffered by the Sponsor due to a flood catastrophic event for 1, 3, and 5 year maturity periods; maintaining the Issuer to earn profits for all simulated catastrophe events; and allowing the Investors to obtain positive returns with high probabilities, although the risk of losing all of the Principal still exists.